Randomized phase 3 study of the anti-disialoganglioside antibody dinutuximab and irinotecan vs irinotecan or topotecan for second-line treatment of small cell lung cancer. (April 2022) - Edelman, Martin J.; Dvorkin, Mikhail; Laktionov, Konstatin; Navarro, Alejandro; Juan-Vidal, Oscar; Kozlov, Vadim; Golden, Gil; Jordan, Odette; Deng, CQ; Bentsion, Dmitriy; Chouaid, Christos; Dechev, Hristo; et al.
Highlights: There has been relatively little progress in the treatment of small cell lung cancer. Disialoganglioside 2 is commonly expressed in SCLC. Dinutuximab, an anti-GD2 antibody is approved for neuroblastoma and is synergistic with irinotecan. Dinutuximab + irinotecan vs. topotecan vs irinotecan in recurrent SCLC did not improve outcomes. Abstract: Introduction: Topotecan is approved as second-line treatment for small cell lung cancer (SCLC). Irinotecan is also frequently used given its more convenient schedule and superior tolerability. Preclinical studies support disialoganglioside (GD2) as an SCLC target and the combination of dinutuximab, an anti-GD2 antibody, plus irinotecan in this setting. We tested dinutuximab/irinotecan versus irinotecan or topotecan as second-line therapy in relapsed/refractory (RR) SCLC. Materials and methods: Patients with RR SCLC and Eastern Cooperative Oncology Group performance status 0–1 were randomized 2:2:1 to receive dinutuximab 16–17.5 mg/m 2 intravenous (IV)/irinotecan 350 mg/m 2 IV (day 1), irinotecan 350 mg/m 2 IV (day 1), or topotecan 1.5 mg/m 2 IV (days 1–5) in 21-day cycles. The primary endpoint was overall survival (OS); secondary endpoints were progression-free survival (PFS), objective response rate (ORR; complete response [CR] + partial response [PR]), and clinical benefit rate (CBR; CR + PR + stable disease). Safety/tolerability were also assessed. Results: A total of 471 patients were randomized to dinutuximab/irinotecan (n = 187), irinotecan (n = 190), or topotecan (n = 94). Age, sex, performance status, prior therapies, and metastatic disease sites were similar between groups. Survival and response rates were not improved for patients receiving dinutuximab/irinotecan versus those receiving irinotecan or topotecan (median OS 6.9 vs 7.0 vs 7.4 months [ p = 0.3132]; median PFS 3.5 vs 3.0 vs 3.4 months [ p = 0.3482]; ORR confirmed 17.1% vs 18.9% vs 20.2% [ p = 0.8043]; and CBR 67.4% vs 58.9% vs 68.1% [ p = 0.0989]), respectively. Grade 3/4 adverse events (≥5% receiving dinutuximab/irinotecan) included neutropenia, anemia, diarrhea, and asthenia. Conclusions: Dinutuximab/irinotecan treatment did not result in improved OS in RR SCLC versus irinotecan alone. Irinotecan administered every 21 days demonstrated comparable activity to topotecan administered daily × 5 every 21 days. ClinicalTrials.gov Identifier. NCT03098030.